PFO-DBT:MEH-PPV:PC71BM Ternary Blend Assisted Platform as a Photodetector - Qayyum Zafar; Zubair Ahmad; Khaulah Sulaiman (Sensors, 2015)
We present a ternary blend-based bulk heterojunction ITO/PEDOT:PSS/PFO-DBT: MEH-PPV:PC71BM/LiF/Al photodetector. Enhanced optical absorption range of the active film has been achieved by blending two donor components viz. poly[2,7-(9,9-di-octyl-fluorene)-alt-4,7-bis(thiophen-2-yl)benzo-2,1,3-thiadiazole] (PFO-DBT) and poly(2-methoxy-5(2'-ethylhexyloxy) phenylenevinylene (MEH-PPV) along with an acceptor component, i.e., (6,6)-phenyl-C71 hexnoic acid methyl ester. The dependency of the generation rate of free charge carriers in the organic photodetector (OPD) on varied incident optical power density was investigated as a function of different reverse biasing voltages. The photocurrent showed significant enhancement as the intensity of light impinging on active area of OPD is increased. The ratio of Ilight to Idark of fabricated device at −3 V was ~3.5 × 104. The dynamic behaviour of the OPD under on/off switching irradiation revealed that sensor exhibits quick response and recovery time of ∼800 ms and 500 ms, respectively. Besides reliability and repeatability in the photoresponse characteristics, the cost-effective and eco-friendly fabrication is the added benefit of the fabricated OPD.